Paraquat poisoning in a medical ward - Santos, José Manuel (1996)
The authors present a retrospective study of paraquat poisoning cases admitted at an Internal Medicine department of a central hospital. This analysis includes a 7.5 years period, involving 26 cases, with male sex predominance (16 patients) and ages between 16 and 74 years old. The mean time elapsed between the toxic ingestion andflrst health care was 1,8 hours if they were admitted in the first 24 hours; three patients arrived later to the hospital. The quantities of poison ingested were variable, but more frequently between 20 and 100 ml Thirteen in-patients were death while the other 13 were discharged from hospital with good health (known middle survi val time of 10 months). The 2 groups were com pared and the single prognostic factor was the ingested quantity of paraquat. Dyspnea, oliguria and jaundice were the clinical manifestations with prognostic value, while values of LDH, AST and pO2 (at admission on Urgency Room) were also prognostic indicators. Any medical measure see med to modify the disease course when a high dose was ingested.